RELIGIOUS MODERATION UNVEILED: The Intersection of Textual and Contextual Approaches to Understanding Indonesian Muslims - Amri, Yaser; Febriandi, Yogi; Da-Oh, Phaison (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This article examines the concept of religious moderation using an intersectional approach to illustrate the disparity in its interpretation between state policies and societal practice. Prior literature has explored religious moderation from doctrinal and security viewpoints. This study proposes a new perspective to enhance the understanding of religious moderation in the Indonesian context by presenting its interpretation through two distinct lenses. First, it examines the concept of religious moderation within the context of daily interactions among religious communities. Second, this article criticizes the state's intervention in religious moderation campaigns. This article argues that religious moderation is inherently intricate, a complexity that finds resonance in the stance adopted by the state and everyday civil practice. The contention here is that the multifaceted nature of religious moderation is not confined to theoretical discourse; it reverberates through the policies enacted by the state and is interwoven with the actions and routines of individuals within the society.